Genome-wide organization of chromatin and the transcription machinery - Pugh, Frank (Henry Stewart Talks, 2014)
Genomics of gene regulation, Chromatin, Canonical nucleosome organization around genes, ChIP-exo mapping of sequence-specific transcription factors, Genomic organization of transcription pre-initiation complexes